MANAJEMEN KEPEGAWAIAN BADAN KEPEGAWAIAN DAERAH, PENDIDIKAN DAN PELATIHAN KABUPATEN KEPULAUAN SANGIHE (STUDI TENTANG PENGANGKATAN PEJABAT STRUKTURAL ESELON IV) - ALING, AGUSTIEN AHUNGSEHIWU; LIANDO, DAUD; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract :The changing work environment is so dynamic, many faced by every organization. Organizations and structures are always required to adapt and move with those changes, automatically changes in the organizational structure also have an impact on the career development of individual employees. In the case of regional personnel, in the implementation of personnel management, especially promotion, mutation and demotion is a phenomenon that often occurs in a regional organization.The process of appointment of echelon IV structural officials in their implementation is technically less relevant to the qualifications required by the organization. The irrelevance of the the position and educational background and the expertise of the appointed officials so it deemed necessary to examine why the personnel management of the regional personnel agency, education and training of the Sangihe islands districts on the appoinment of the echelon IV structural officials has not gone wellThis research is descriptive qualitative research using POAC management function theory proposed by George R.Terry as the guideline of this research, but the problems encountered in the related field are the indicators of planning and organizing while the indicators of actuating and controlling there is no problem in the field.                The results showed that the implementation of the appoinment of echelon IV structural officials was not fully in accordance with the mechanism and procedure of appointment of civil servants in structural positions as regulated in the government regulation because in the process of conducting the assesment subjectively, and not apart from the policy of position consideration agency and the rank and officer of staffing officers who accommodate officials through the proximity of the relationship and  family                From the results of this study then suggested some things include : local goverment sangihe archipelago should minimize the policies and interventions that cause the appoinment of structural officials to be not objective. Staffing officers should develop the mechanism of appoinment of officials through the stages in accordance with existing rules by merit system, by placing the right people, and optimizing the implementation of education and training for stuctural officials by allocating more funds for education and training activities so that through the provision of education and training will be positively correlated to impact on improvements to quality improvement, the ability of echelon IV structural officials in carrying out the work so as to give a tangible contribution to the region. Keyword : Management, Staffing Agencies Staffing areas, education and training